The apothecary order – the origin and formation. Part 5 - K. S. Guzev (Разработка и регистрация лекарственных средств)
The fifth part of the article provides information about the function of the Apothecary prikaz to supply the Russian state with medicinal plant raw materials. Medicinal plants were purchased abroad, in Moscow merchant’s rows, and were also cultivated and introduced in apothecary gardens. Over time, more and more attention was paid to this work of the Apothecary prikaz, and this function gradually became a duty.